Twins, Family Size, and Female Labor Force Participation in Iran - Mahdi Majbouri (Institute of Labor Economics (IZA), 2018)
Despite the remarkable increase in women's education levels and the rapid fall of their fertility rate in Iran, female labor force participation (FLFP) has remained low. Using the instrumental variable method, this paper estimates the causal impact of number of children on mothers' participation in the labor market. It finds that having an extra (unplanned) child would only reduce female participation rate for low educated mothers and mothers with young children, thus having no causal impact on most mothers' participation. This result explains why the rapid decline in fertility rates did not increase female participation; rather, other factors should be at play. It hence moves us a step forward in explaining the puzzle of female labor force participation in Iran. Policy implications are discussed.
Keywords: J13; J22; O53; 330; female labor force participation; fertility; Iran; twins; instrumental variable